Upaya Pencegahan Nyeri Sendi dengan Implementasi Latihan Progressive Muscle Relaxation Berbasis Arduino Uno pada Kemampuan Motorik Lansia Kelurahan Medan Sunggal di Era Pandemi Covid-19 - Eqlima Elfira; Bina Melvia Girsang; Lukman Hakim (Jurnal Pengabdian Pada Masyarakat, 2021)
EFFORTS TO PREVENT JOINT PAIN WITH THE IMPLEMENTATION OF ARDUINO UNO-BASED PROGRESSIVE MUSCLE RELAXATION EXERCISES IN MEDAN SUNGGAL VILLAGE. Arduino Uno-based joint pain prevention efforts are a tool to detect muscle strength with an electromyogram that is connected via a smartphone application. The results of the recording on several muscles that experience joint pain such as hands, feet will experience a sensor signal that is read by CMRR (0-500 Hz) around -92 dB, dimensions 41x20x5mm. The purpose of this implementation is to provide stimulation to the Arduino Uno-based device attached to the arm and leg muscles which produces an Electromyogram (EMG) sensor signal recording. The recordings will show the extent to which the muscles can interact with progressive muscle relaxation exercise movements and provide a relaxing effect to the participants. This service activity was attended by 39 elderly people who have a history of joint pain due to comorbidities such as sugar, cholesterol, and uric acid in Medan Sunggal village. Retrieval of data using a smartphone application that is stored automatically during implementation. This service activity produces a muscle detector and therapy device that provides a relaxing effect on breathing when doing progressive muscle relaxation exercises. This is evidenced by the response of the participants with this activity helping to carry out progressive muscle relaxation training activities every day at home.